Iodine Levels and Thyroid Hormones in Pregnant Women and Neonatal Outcomes: A Systematic Review: Iodine Levels and Thyroid Hormones in Pregnant Women and Neonatal Outcomes - Ashraf, Seema; Ishraq, Muhammad; Khan, Mashal Irshad; Kalsoom, Ommia; Ijaz, Azhar; Farukh, Umair (Pakistan Journal of Health Sciences, 2025)
Iodine plays a vital role in the synthesis of thyroid hormones, which are essential for fetal growth and brain development. During pregnancy, maternal iodine needs to increase. Both deficiency and excess can impair maternal thyroid function and lead to complications such as hypothyroxinemia, fetal growth restriction, or thyroid dysfunction in the mother or child. Objectives: To assess the relationship between maternal iodine levels, thyroid function, and neonatal outcomes, and highlight the risks associated with both iodine deficiency and excess. Methods: A systematic search was conducted in PubMed, Web of Science, Scopus, Springer, and MDPI for studies published from 2021 to 2025. Inclusion criteria involved studies assessing iodine status (Urinary Iodine Concentration (UIC) or Serum Iodine Concentration (SIC)), maternal thyroid function (TSH, FT4, FT3), and neonatal outcomes. Articles were screened using PRISMA guidelines. The risk of bias was assessed using the Newcastle-Ottawa Scale and Cochrane Risk of Bias Tool. Due to heterogeneity in methods and outcomes, results were narratively synthesized. Results: Ten studies were included. Iodine deficiency was consistently associated with low birth weight and disrupted thyroid hormone levels, while iodine excess particularly at levels ≥500 µg/L was linked to transient neonatal hyperthyrotropinemia. Environmental exposures such as endocrine-disrupting chemicals also influence maternal thyroid function. Conclusions: It was concluded that both iodine deficiency and excess pose risks to maternal and neonatal thyroid health. Routine monitoring and individualized supplementation based on regional dietary patterns and environmental exposures are recommended.